Improvement in Total Joint Replacement Quality Metrics: Year One Versus Year Three of the Bundled Payments for Care Improvement Initiative. (7th December 2016) - Dundon, John M.; Bosco, Joseph; Slover, James; Yu, Stephen; Sayeed, Yousuf; Iorio, Richard
Abstract : Background: In January 2013, a large, tertiary, urban academic medical center began participation in the Bundled Payments for Care Improvement (BPCI) initiative for total joint arthroplasty, a program implemented by the Centers for Medicare & Medicaid Services (CMS) in 2011. Medicare Severity-Diagnosis Related Groups (MS-DRGs) 469 and 470 were included. We participated in BPCI Model 2, by which an episode of care includes the inpatient and all post-acute care costs through 90 days following discharge. The goal for this initiative is to improve patient care and quality through a patient-centered approach with increased care coordination supported through payment innovation. Methods: Length of stay (LOS), readmissions, discharge disposition, and cost per episode of care were analyzed for year 3 compared with year 1 of the initiative. Multiple programs were implemented after the first year to improve performance metrics: a surgeon-directed preoperative risk-factor optimization program, enhanced care coordination and home services, a change in venous thromboembolic disease (VTED) prophylaxis to a risk-stratified protocol, infection-prevention measures, a continued emphasis on discharge to home rather than to an inpatient facility, and a quality-dependent gain-sharing program among surgeons. Results: There were 721 Medicare primary total joint arthroplasty patients in year 1 and 785 in year 3; their data were compared. The average hospital LOS decreased from 3.58 to 2.96 days. The rate of discharge to an inpatient facility decreased from 44% to 28%. The 30-day all-cause readmission rate decreased from 7% to 5%; the 60-day all-cause readmission rate decreased from 11% to 6%; and the 90-day all-cause readmission rate decreased from 13% to 8%. The average 90-day cost per episode decreased by 20%. Conclusions: Mid-term results from the implementation of Medicare BPCI Model 2 for primary total joint arthroplasty demonstrated decreased LOS, decreased discharges to inpatient facilities, decreased readmissions, and decreased cost of the episode of care in year 3 compared with year 1, resulting in increased value to all stakeholders involved in this initiative and suggesting that continued improvement over initial gains is possible.